Optimum temperature on structural growth of multiwalled carbon nanotubes with low activation energy - Shukrullah, S. (Elsevier Ltd, 2015)
Abstract This study deals with the catalytic decomposition of ethylene over Fe2O3/Al2O3 catalyst for the nucleation of nanotubes at growth temperature of 700 to 950 °C. The motivation for conducting this work was primarily an interest in growing a better yield of well-structured MWCNTs by making use of the minimum activation energy. A vertically fluidize bed reactor was used to accomplish the experimental work on production of nanotubes. The final product was characterized using a set of imaging, spectroscopic and statistical tools. The required activation energy of the reaction was reduced down to 19.5 kJ/mol. This decrease in activation energy was attributed to Al2O3 promoter and high density of the active sites on the surface of the chemically activated catalyst. Descriptive statistics on the tube diameter distribution revealed the formation of positively skewed histograms at 700 to 800 °C, negatively skewed histograms at 850 to 900 °C and symmetrically skewed histogram at 950 °C. The highest coefficient of variation of 14.5 was calculated in diameter distribution of CNTs grown at 950 °C. A narrow diameter distribution with ideally graphitized tube structures was predicted at the optimum growth temperature of 800 °C. ID/IG and IG'/IG ratios and the product weight loss calculated from the Raman spectra and approximate analyses, respectively, confirmed the growth of 94 pure MWCNTs. © 2015 Elsevier B.V.